2017
DOI: 10.1186/s12871-017-0459-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of amiodarone in a mouse model of ischemic stroke

Abstract: BackgroundIon channels play a crucial role in the development of ischemic brain injury. Recent studies have reported that the blockade of various types of ion channels improves outcomes in experimental stroke models. Amiodarone, one of the most effective drugs for life-threatening arrhythmia, works as a multiple channel blocker and its characteristics cover all four Vaughan-Williams classes. Although it is known that amiodarone indirectly contributes to preventing ischemic stroke by maintaining sinus rhythm in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…In addition to working directly on cardiac tissue to reverse the ventricular arrhythmia, Amiodarone has been shown to alter cerebral chemical channels too [53]. Using a stroke mouse model, Kotoda et al [53] showed that the administration of Amiodarone prior to initiating a stroke was neuroprotective.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to working directly on cardiac tissue to reverse the ventricular arrhythmia, Amiodarone has been shown to alter cerebral chemical channels too [53]. Using a stroke mouse model, Kotoda et al [53] showed that the administration of Amiodarone prior to initiating a stroke was neuroprotective.…”
Section: Discussionmentioning
confidence: 99%
“…The Blockade of sodium channels can also be neuroprotective. As we previously reported, pre-treatment, but not post-treatment, with amiodarone attenuates brain injury after ischemic stroke by blocking the voltage-gated sodium channel [12]. Whether amiodarone acts on the neuroprotective side or detrimental side is likely to be dependent on the clinical and pathophysiological condition.…”
Section: Discussionmentioning
confidence: 97%
“…Two mice were excluded due to the death before 24 h after induction (one per each group); eight mice were included in each group. The amiodarone dose was chosen based on the body surface area [11] and previously published data [12]. The rectal temperature was monitored and maintained at 37 ± 0.5 °C using a heating pad.…”
Section: Methodsmentioning
confidence: 99%
“…Only turns involving full rearing along either board were recorded. This test was used to assess the sensorimotor and postural function [28].…”
Section: Methodsmentioning
confidence: 99%